Heat-induced structural changes affect OVA-antigen processing and reduce allergic response in mouse model of food allergy - Golias, Jaroslav; Schwarzer, Martin; Wallner, Michael; Kverka, Miloslav; Kozakova, Hana; Srutkova, Dagmar; Klimesova, Klara; Sotkovsky, Petr; Palova-Jelinkova, Lenka; Ferreira, Fatima; Tuckova, Ludmila (PloS one, 2012)
BACKGROUND AND AIMS: The egg protein ovalbumin (OVA) belongs to six most frequent food allergens. We investigated how thermal processing influences its ability to induce allergic symptoms and immune responses in mouse model of food allergy. METHODOLOGY/PRINCIPAL FINDINGS: Effect of increased temperature (70°C and 95°C) on OVA secondary structure was characterized by circular dichroism and by the kinetics of pepsin digestion with subsequent HPLC. BALB/c mice were sensitized intraperitoneally and challenged with repeated gavages of OVA or OVA heated to 70°C (h-OVA). Levels of allergen-specific serum antibodies were determined by ELISA (IgA and IgGs) or by β-hexosaminidase release test (IgE). Specific activities of digestive enzymes were determined in brush border membrane vesicles of jejunal enterocytes. Cytokine production and changes in regulatory T cells in mesenteric lymph nodes and spleen were assessed by ELISA and FACS. Heating of OVA to 70°C caused mild irreversible changes in secondary structure compared to boiling to 95°C (b-OVA), but both OVA treatments led to markedly different digestion kinetics and Tregs induction ability in vitro, compared to native OVA. Heating of OVA significantly decreased clinical symptoms (allergic diarrhea) and immune allergic response on the level of IgE, IL-4, IL-5, IL-13. Furthermore, h-OVA induced lower activities of serum mast cell protease-1 and enterocyte brush border membrane alkaline phosphatase as compared to native OVA. On the other hand h-OVA stimulated higher IgG2a in sera and IFN-γ secretion by splenocytes. CONCLUSIONS: Minor irreversible changes in OVA secondary structure caused by thermal processing changes both its digestion and antigenic epitopes formation, which leads to activation of different T cell subpopulations, induces shift towards Th1 response and ultimately reduces its allergenicity.
Keywords: sekundární struktura proteinů; potravinová alergie; Immunoglobulin E; prezentace antigenu; ovalbumin; Ovalbumin; Antigen Presentation; cytokiny; Disease Models, Animal; vysoká teplota; Food Hypersensitivity; regulační T-lymfocyty; Mice; Cytokines; T-Lymphocytes, Regulatory; modely nemocí na zvířatech; ženské pohlaví; Protein Structure, Secondary; zvířata; imunoglobulin E; Hot Temperature; myši; Female; Animals